1993
DOI: 10.1111/j.1440-1754.1993.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anencephalus and spina bifida in New Zealand

Abstract: Despite the plethora of epidemiological research conducted on anencephalus and spina bifida, few of the studies have used multiple source case ascertainment and controlled for the effect of possible confounding factors. This paper reports the results from a study of the relationships between various risk factors and the prevalence of anencephalus and spina bifida in New Zealand during 1978-82, using case data obtained from multiple sources and a national cohort of births as the denominator. The rates of anence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…From Table 2 it can also be seen that an increase of 0.4 mg folic acid daily could prevent 84 (95% CI 50-130) NTDs in Australia and 18 (95% CI [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in New Zealand, a 25% reduction in NTDs.…”
Section: Resultsmentioning
confidence: 99%
“…From Table 2 it can also be seen that an increase of 0.4 mg folic acid daily could prevent 84 (95% CI 50-130) NTDs in Australia and 18 (95% CI [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] in New Zealand, a 25% reduction in NTDs.…”
Section: Resultsmentioning
confidence: 99%
“…We found that there was no significant association between paternal age and the risk of NTD. Independent studies from New Zealand, California and Texas demonstrated no relationship between paternal age and anencephaly or spina bifida or encephalocele 27,32,33 . Some studies, however, suggest that paternal age may indeed be a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Independent studies from New Zealand, California and Texas demonstrated no relationship between paternal age and anencephaly or spina bifida or encephalocele. 27,32,33 Some studies, however, suggest that paternal age may indeed be a risk factor. For example, the data from the British Columbia Health Surveillance Registry demonstrated a general trend of increasing risk with increasing paternal age, but interestingly, men under 20 years of age were also at increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no published data on the rate of NTD among different ethnic groups in New Zealand exists post-introduction of periconceptional folic acid supplementation recommendations. However, reports from the late 1970's and early 1980's indicate that the rate of NTD was lower among Pacific and Māori women compared with non-Māori [29]. …”
Section: Discussionmentioning
confidence: 99%